The Cultural Meaning Effect to Functional Vitality of a Historical Site was Developed into Urban Public Green Open Space - Broto W Sulistyo; Antariksa; Surjono; Luchman Hakim (Technium Social Sciences Journal, 2020)
Characteristics and cultural understanding of visitors, was developed into a public green open space (PGOS). Urban PGOS is one of the elements that form the shape of the city. On the other hand, in the context of historical and cultural developments, public spaces in smaller cities or areas are the center of social activity as a pragmatic space for social and cultural interaction. As a result, social interaction function becomes the first function and there is a shift from a communal into a more individualized function of exposure or exhibition. These differences lead to a shift in the function and meaning of the function, as well as the existence of the public space, causing a redefinition of the public space where the soul is located. The addition of new functions, which have different characters and characteristics, to the existing functions, is necessary to examine in-depth, especially the use and understanding of adding functions so that the public open green space and the historic site in it can still be run in the corridor expected to provide public space appropriately in terms of principle and popular culture context. However, over time, the urban public green open space has experienced a shift because the function of the initial idea was built first with the phenomenon of the utilization and meaning of space by the community that existed before. This paper presents a critical analysis of how the design of the public open green space design developed from a historic site forms the dynamics of cultural meaning, how the historical site survives its functional vitality, and how important the place is in the realm of meaning to be built.